Tribology in machine design - Stolarski, Tadeusz (Oxford : Elsevier Science, 1999)
"Tribology in Machine Design" is strongly recommended for machine designers, and engineers and scientists interested in tribology. It should be in the engineering library of companies producing mechanical equipment. Applied Mechanics ReviewTribology in Machine Design explains the role of tribology in the design of machine elements. It shows how algorithms developed from the basic principles of tribology can be used in a range of practical applications within mechanical devices and systems.
Introduction to the concept of tribodesign -- Basic principles of tribology -- Elements of contact mechanics -- Friction, lubrication and wear in lower kinematic pairs -- Sliding-element bearings -- Friction, lubrication and wear in higher kinematic pairs -- Rolling-contact bearings -- Lubrication and efficiency of involute gears.
Includes index.
Keywords: Machine design; Tribology; Electronic books